A1 protein free milk benefits mood and subjective cognition in free-living Australian adults: a pragmatic, exploratory, open label randomised controlled trial - Carlene Starck; Michelle Blumfield; Peter Petocz; Emily Duve; Lucy Downey; Kylie Abbott; Flavia Fayet-Moore; Flavia Fayet-Moore (Frontiers in Nutrition)
BackgroundAdverse effects of milk containing A1-type β-casein on digestion, immune response, and cognition have been identified in milk-intolerant individuals, but health effects in healthy individuals without symptoms of milk intolerance are yet to be examined.ObjectiveThe objective was to explore the impact of reducing A1 type β-casein intake via switching milk type from conventional A1/A2-type β-casein milk (A1/A2 milk) to A1-type β-casein protein free milk (A1PF) on brain, immune response, gastrointestinal, and skin (BIGS) outcomes in a real-world setting.MethodsAn open-label, pragmatic, exploratory randomised controlled trial was conducted in 997 healthy, free-living Australian older adolescents and adults (16–65 years) who regularly consume A1/A2 protein-containing milk and milk products. Participants were randomised into two groups, to consume ≥250 mL/day of A1/A2 milk (control) or to switch to ≥250 mL/day of A1PF milk (intervention) for 28 days, while continuing to follow their usual diet (including up to 1 serve a day of A1/A2 dairy products). A sub-group of 265 participants conducted stool, saliva and cognitive testing on days 0 and 28. All participants completed subjective questionnaires on days 0, 14, and 28.ResultsNo differences in gut microbiome composition, alpha-diversity, or function were found by switching milk type. After switching to A1PF milk, a small increase in stool consistency was reported (−0.16, p = 0.007), and females experienced a marginal reduction in gastrointestinal symptoms (p = 0.015) and improved subjective cognition (p = 0.03). Switching to A1PF milk reduced anxiety (−0.61; p = 0.002), depression (−0.56; p = 0.023), stress (−0.70, p = 0.012) and fatigue (p = 0.001; females only), compared to drinking A1/A2 milk, with stronger effects in females. No consistent effects on markers of immune response or skin health were identified.ConclusionSwitching from conventional A1/A2 milk to A1PF milk may benefit mood and subjective cognition, particularly in females, without the need for complete elimination of A1 β-casein from the diet. Further investigations are warranted.Clinical trial registrationhttps://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=385966, identifier ACTRN12623000628640.